Biodiversity of fruit plants (edibles) at the Kentingan Campus of Universitas Sebelas Maret, Surakarta, Central Java, Indonesia - Afifah, Ratih Nur; Rezapratama, Muhammad Syavy; Isa, Mukhlisah Nadya; Nugroho, Gilang Dwi; Setyawan, Ahmad Dwi (Generasi Biologi Indonesia, 2023)
Urban areas have the potential to support food supply even in limited quantities due to limited green open land, including edible fruits. This study aims to determine the biodiversity of fruit plants (edibles) at the Kentingan Campus of Universitas Sebelas Maret (UNS), Surakarta, Central Java, Indonesia. Data were collected by survey methods with cruising techniques, accompanied by a calculation of the ecological index in December 2022. Survey methods with cruising techniques, namely by exploring the entire campus area to collect the required primary data, including the name of plant species, the number of individuals, coordinates and fruit documentation found from each species. Data is processed and analyzed using the calculation of the ecological index. Meanwhile, secondary data was obtained from IUCN to determine the status of conservation and Plants of the World Online to determine the authenticity of species. The results obtained that there are 55 species from 25 families fruit plants with the Shannon-Wiener Index in the medium category, which is 3.17. Furthermore, the Margalef Index is in the high category, which is 7.30, and the Simpson Dominance Index is in a low category, which is 0.077. Some species have the highest number of individuals, namely Musa x paradisiaca L. (Musaceae), with 327 individuals. On the other hand, Mangifera indica L. (Anacardiaceae) is a species found in all locations. From the data obtained, according to IUCN, there are several fruit plants with 23 species of Least Concern (LC) conservation status and Data Deficient (DD) conservation status, as many as two species. Meanwhile, based on data from Plants of the World Online, several fruit plants on the Kentingan Campus of UNS are native to Indonesian plants, namely Durio zibethinus Murray, Averrhoa bilimbi L, and Averrhoa carambola L.